Revisiting the neuro-turn in the humanities and natural sciences - Budtz Pedersen, David (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
In the last twenty years there has been an unprecedented advance in neuroscience, infields such as pharmacology, neurology and behavioural genetics. A growing number of ethicists, legal scholars and philosophers have begun to analyse the implications of these advances; from the use off MRI scanning to the way in which scientific disciplines are organised in order to deliver techno-economic innovation. Drawing on recent contributions in philosophy of science and science policy studies I arguethat much like the optimism surrounding the benefit of advances in pharmaco genomics and gene therapy, there is a risk of overstating the real impact and explanatory power of advances in the neurosciences.